Segmentasi Baris Lontar Dengan Metode A * Path Planning - Dewi Lestari, Anak Agung Istri; Astawa, I Gede Santi; Sanjaya ER, Ngurah Agus; Suputra, I Putu Gede Hendra; Pramartha, Cokorda Rai Adi; Supriana, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 2 (2022): JELIKU Volume 11 No 2, November 2022DO - 10.24843/JLK.2022.v11.i02.p14, 2022)
Historical documents in the form of ancient manuscripts are one form of the Indonesian nation's cultural heritage that deserves to be important, one of which is Lontar. Currently not many people can read the writings in palm leaves, therefore, ancient manuscript collectors have made efforts to digitize ancient manuscripts. The digitization of ancient manuscripts aims to improve the image quality of ancient manuscripts with the help of computers. Digitization requires an image quality improvement process by performing noise reduction and edge detection and line segmentation on digital images of ancient manuscripts. In this study, the noise reduction process uses the Mean Filter method, edge detection uses the Sobel operator, and line segmentation in this study uses the A * Path Planning Algorithm. Based on research conducted on 24 lontar images, line segmentation process obtained an accuracy of 95%.